2009
DOI: 10.1097/mop.0b013e32832f5b9d
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric celiac disease

Abstract: This review aims at outlining the different manifestations of celiac disease in children as well as a step-wise approach to screen and diagnose the disease. A better understanding of the pathogenic mechanisms of celiac disease is paving the way to innovative diagnostic tools, preventive strategies, and therapeutic interventions alternative to a gluten-free diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 29 publications
1
33
0
6
Order By: Relevance
“…[1][2][3] CD is caused by an inflammatory T-cell response to the storage proteins in wheat (gliadin), rye (secalin) and barley (hordein), which are collectively called gluten. Large-scale screening studies in the general population have shown a CD prevalence of nearly 0.5-1.0% in both adults and children.…”
Section: Mass Screening Of CD In Young Childrenmentioning
confidence: 99%
“…[1][2][3] CD is caused by an inflammatory T-cell response to the storage proteins in wheat (gliadin), rye (secalin) and barley (hordein), which are collectively called gluten. Large-scale screening studies in the general population have shown a CD prevalence of nearly 0.5-1.0% in both adults and children.…”
Section: Mass Screening Of CD In Young Childrenmentioning
confidence: 99%
“…Research suggests that CD is a relatively common diagnosis, with estimates approximating nearly 1 in 100 children living with CD, although many cases remain undiagnosed in part due to the heterogeneity of symptom presentation [45][46][47]. As previously noted, the primary treatment for the disorder is life-long adherence to a gluten-free diet.…”
Section: Celiac Diseasementioning
confidence: 95%
“…As previously noted, the primary treatment for the disorder is life-long adherence to a gluten-free diet. Compliance with such a stringent diet has been shown to be problematic and challenging to many children and adolescents with CD [7,47,48], and may put children and adolescents at an increased risk for the development of eating pathology.…”
Section: Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of these symptoms are mainly seen in young children (Zawahir 2009, Lionetti 2011). …”
Section: Clinical Features and Demographicsmentioning
confidence: 99%